1+2+...+n+(n-1)+...+1 = n^2/Proof 2

From ProofWiki
Jump to navigation Jump to search

Theorem

$\forall n \in \N: 1 + 2 + \cdots + n + \left({n-1}\right) + \cdots + 1 = n^2$


Proof

\(\displaystyle \) \(\) \(\displaystyle 1 + 2 + \cdots + \paren {n - 1} + n + \paren {n - 1} + \cdots + 1\)
\(\displaystyle \) \(=\) \(\displaystyle \paren {1 + 2 + \cdots + \paren {n - 1} } + \paren {1 + 2 + \cdots + \paren {n - 1} + n}\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {\paren {n - 1} n} 2 + \frac {n \paren {n + 1} } 2\) Closed Form for Triangular Numbers
\(\displaystyle \) \(=\) \(\displaystyle \frac {n^2 - n + n^2 + n} 2\)
\(\displaystyle \) \(=\) \(\displaystyle n^2\)

$\blacksquare$